Comparative diagnostic performance of imaging modalities in chronic pancreatitis: a systematic review and Bayesian network meta-analysis - Ping Yu; Xujia Zhou; Li Yue; Ling Zhang; Yuan Zhou; Fei Jiang (BMC Medical Imaging)
Abstract Purpose We aimed to perform a Bayesian network meta-analysis to assess the comparative diagnostic performance of different imaging modalities in chronic pancreatitis(CP). Methods The PubMed, Embase and Cochrane Library databases were searched for relevant publications until March 2024. All studies evaluating the head-to-head diagnostic performance of imaging modalities in CP were included. Bayesian network meta-analysis was performed to compare the sensitivity and specificity between the imaging modalities. The Quality Assessment of Diagnostic Performance Studies (QUADAS-2) tool was used to evaluate the quality of studies. Results This meta-analysis incorporated 17 studies. Network meta-analytic results indicated that endoscopic ultrasonography (EUS) achieved the highest surface under the cumulative ranking (SUCRA) value at 0.86 for sensitivity. Conversely, magnetic resonance imaging (MRI) demonstrated best specificity, recording the highest SUCRA value at 0.99. Ultrasonography (US) displayed comparatively lower sensitivity than endoscopic retrograde cholangiopancreatography (ERCP) (relative risk[RR]: 0.83, 95% Confidence Interval[CI]: 0.69–0.99) and EUS (RR: 0.73, 95% CI: 0.57–0.91). MRI outperformed all other imaging modalities in terms of specificity. Conclusions It appears that EUS demonstrates higher sensitivity, while MRI exhibits higher specificity in patients with chronic pancreatitis. However, it is crucial to note that our analysis was limited to the diagnostic performance and did not evaluate the cost-effectiveness of these various imaging modalities. Consequently, further extensive studies are needed to assess the benefit-to-risk ratios comprehensively.